When the emperor dies - Smith, Mason McCann, 1952- (Hamilton, 1982)
In 1868 Queen Victoria's empire was at the height of its worldly power. One nation stood against British dominion; Ethiopia where Emperor Theodore held British subjects captive and thought he had a chance to deliver his people from British rule. [By publisher]